2014
DOI: 10.1175/jhm-d-13-096.1
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Rainfall Downscaling of Climate Models

Abstract: Precipitation extremes and small-scale variability are essential drivers in many climate change impact studies. However, the spatial resolution currently achieved by global climate models (GCMs) and regional climate models (RCMs) is still insufficient to correctly identify the fine structure of precipitation intensity fields. In the absence of a proper physically based representation, this scale gap can be at least temporarily bridged by adopting a stochastic rainfall downscaling technique. In this work, a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…In addition, the proposed framework can not only be used to downscale historical precipitation data like in this study, but also for future prediction, e.g., for downscaling the output of Global Circulation Models (GCM) at regional scales [74]. Moreover, it is also applicable in other areas of hydrology such as soil moisture downscaling [75].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the proposed framework can not only be used to downscale historical precipitation data like in this study, but also for future prediction, e.g., for downscaling the output of Global Circulation Models (GCM) at regional scales [74]. Moreover, it is also applicable in other areas of hydrology such as soil moisture downscaling [75].…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, RCMs have been long ago employed to analyze climate dynamics across different spatial scales (e.g., Giorgi 1990;Deque and Piedelievre 1995). In fact, several recent studies demonstrated the benefits from the use of RCMs in reproducing climate patterns at local scales within the MR and for improving the quality of input data for impact studies in areas of complex geography (Flaounas et al 2013;Guyennon et al 2013;D'Onofrio et al 2014;Calmanti et al 2015). Despite their ability to resolve fine-scale atmospheric features, RCM results are associated with significant uncertainties.…”
mentioning
confidence: 99%
“…RnormM provides the monthly precipitation sums over the standard period 1981-2010, calculated from the data of all automatic and manual stations in Switzerland, achieving high accuracy and detailed spatial resolution. The RainFARM procedure is described in detail in Rebora et al (2006) andD'Onofrio et al (2014), and in the present paper we refer to the spatial-only downscaling method described in the latter. The RainFARM method downscales a large-scale spatio-temporal precipitation field P (X, Y, t), which is considered reliable at scales larger than a reliability scale L o (which often may coincide with the spatial resolution of the field).…”
Section: Meteoswiss Station and Gridded Datamentioning
confidence: 99%